Pengaruh Pelatihan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada BPR Bumi Prima Dana di Tabanan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Training for companies is very important in advancing employee performance, especially with the existence of work discipline can grow employee performance higher, so BPR Bumi Prima Dana strives to provide financial training that suits employee needs and maintains a level of work discipline in order to improve employee performance. The purpose of this study is to determine the effect of job training and work discipline on employee performance at BPR Bumi Prima Dana in Tabanan. This research was conducted at BPR Bumi Prima Dana in Tabanan with a total sample of 31 people using a saturated sample determination method. The data collection method uses observation, interviews and questionnaires conducted to respondents. The data analysis techniques used are multiple linear regression analysis, determination coefficient test, t test and F test. The results in this study can be concluded that partially job training has a positive and significant effect on employee performance at BPR Bumi Prima Dana in Tabanan. Partially, work discipline has a positive and significant effect on employee performance at BPR Bumi Prima Dana in Tabanan. And simultaneously job training and work discipline have a positive and significant effect on employee performance at BPR Bumi Prima Dana in Tabanan. Good advice given from this study is to increase the amount of financial training for employees, set sanctions for employees who are late and violate work rules and foster creativity at work.